164k views
0 votes
Please help! I don’t understand this!

Please help! I don’t understand this!-example-1
User MissT
by
6.1k points

2 Answers

5 votes

Answer:

f(3) = 13

Explanation:

Given f(x) = 2
x^(2) -3x + 4

For f(3), solve by using the polynomial remainder theorem, need to dive by (x-3) because the remainder theorem says if a polynomial f(x) is divided by x-r, the remainder is a constant f(r);

therefore f(3) = 13 (see image attached)

Please help! I don’t understand this!-example-1
User Samuel Hsieh
by
6.3k points
3 votes

Answer:

f(3)=13

Explanation:

F(x)=2x^2 -3x+4

f(3)= 2(3)^2 -3(3) +4

f(3)= 2(9) -(9) +4

f(3)= 18-9+4

f(3)=9+4

f(3)=13

User Sitz Blogz
by
5.1k points